Seismic Behavior of a Novel Buckling-Restrained Steel Plate Shear Wall - Yang Li; Xiaofeng Zhao; Ping Tan; Fulin Zhou; Jin Jiang (Shock and Vibration)
In this study, in a novel buckling-restrained steel plate shear wall (BRSPSW) with out-of-plane deformation spaces, angle steel stiffeners have been installed so as to create gaps between the steel plate and the covering concrete slabs. A finite element model has been developed to analyse the effect of the gap. According to the finite element results, seismic performance of this novel BRSPSW has been tested under cyclic loading at the scale ratio of 1/3. The failure pattern, hysteretic characteristics, skeleton curve, equivalent stiffness, ductility, and energy dissipation have all been systematically analysed. A stiffened steel plate shear wall (SPSW) has also been tested in order to determine the differences between these two steel shear walls in load-carrying capability and the function and significance of the gap. The test results show that the novel BRSPSW does not only significantly enhance the ultimate bearing capacity, stiffness, ductility, and accumulated energy dissipation of the SPSW but also keep the steel plate basically intact at the end of the test. This can be attributed to the existence of the gaps between the infilled steel plate and the covering concrete slabs. The hysteretic characteristics and the strength and deformation characteristics of this novel BRSPSW have been simulated by using the finite element model, and the test results are in good agreement with the finite element results. Hence, the BRSPSW is an excellent steel plate shear wall to be used in high rise structure to resist horizontal loadings.